N2 HOMO-1 orbital cross section revealed through high-order-harmonic generation - Troß, Jan; Ren, Xiaoming; Makhija, Varun; Mondal, Sudipta; Kumarappan, Vinod; Trallero-Herrero, Carlos. A. (My University, 2017)
We measure multi-orbital contributions to high harmonic generation from aligned nitrogen. We show that the change in revival structure in the cutoff harmonics has a counterpart in the angular distribution when a lower-lying orbital contributes to the harmonic yield. This angular distribution is directly observed in the laboratory without any further deconvolution. Because of the high degree of alignment we are able to distinguish angular contributions of the highest occupied molecular orbital 1 (HOMO-1) orbital from angle-dependent spectroscopic features of the HOMO. In particular, we are able to make a direct comparison with the cross section of the HOMO-1 orbital in the extreme ultraviolet region. © 2017 American Physical Society.
Citation: Troß, J., Ren, X., Makhija, V., Mondal, S., Kumarappan, V., & Trallero-Herrero, C. A. (2017). N2 HOMO-1 orbital cross section revealed through high-order-harmonic generation. Physical Review A - Atomic, Molecular, and Optical Physics, 95(3). doi:10.1103/PhysRevA.95.033419
Keywords: Harmonic Analysis; Harmonic Generation; Molecular Orbitals; Angle-Dependent; Degree Of Alignments; Extreme Ultraviolet